Agreement between measured weight, height and BMI and Web-based self-reported data in participants of the 1993 Pelotas Birth Cohort, Brazil: a cross-sectional validation study - Vivian Hernandez Botelho; Aluísio J. D. Barros; Renata Gonçalves de Oliveira; Rafaela Costa Martins; Helen Gonçalves; Ana M. B. Menezes; Cauane Blumenberg (Ministério da Saúde do Brasil, 2023)
ABSTRACT Objective: to evaluate the agreement between measured height, weight, and body mass index (BMI) during the 22-year follow-up of the 1993 Pelotas Birth Cohort, state of Rio Grande do Sul, Brazil, and self-reported data during the online follow-up of the coortesnaweb. Methods: this was a cross-sectional validation study; agreement was assessed by means of Lin's concordance correlation coefficient for continuous measures and weighted Kappa for nutritional status; Spearman's rank correlation coefficient was used to estimate the correlation between measurements. Results: a total of 783 participants were included; it could be seen high correlation and high agreement between the measured height (r = 0.966; ρ = 0.966), weight (r = 0.934; ρ = 0.928), and BMI (r = 0.903; ρ = 0.910) and Web-based self-reported data; there was no correlation between mean difference and the time interval between measurements. Conclusion: using the Internet to collect self-reported anthropometric measurements is as valid as the traditional method.